Growth and characterization of КН₂РО₄ single crystals doped with ТіO₂ nanocrystals - Pritula, I.; Gayvoronsky, V.; Kopylovsky, M.; Kolybaeva, M.; Puzikov, V.; Kosinova, A.; Tkachenko, V.; Tsurikov, V.; Konstantiniva, T.; Pogibko, V. (Functional Materials, 2008)
For the first time, the method of temperature lowering was used to grow KDP single crystals from aqueous solutions containing TiO₂ (anatase) nanocrystals. The concentration of TiO₂ in the initial solution varied from 10⁻³ to 10⁻⁵ M/l. Using the method of three-crystal X-ray diffractometry, the presence of turns of the growth layer packets ~ 3 arcsec was revealed in KDP:TiO₂ crystals for the sectors {100} and {101}. The observed thickness of the growth packets was on the order of 20-30 μm. There was found the sixfold rise of the crystal lattice parameters Δd/d in the doped crystal relatively to the pure one caused by incorporation of the nanoparticles into the boundaries of layer-bylayer growth and a formation of semicoherent bond with the crystal. It was found the effect of giant nonlinear optical response of anatase nanoparticles manifestation in KDP crystalline matrix. Методом зниження температури вперше вирощено кристали KDP з водних розчинів, що містять нанокристали TiO₂ (анатазу). Концентрація TiO₂ варіювалася у початковому розчині від 10⁻³ до 10⁻⁵ М/л. У кристалах KDP:TiO₂ методом трьохкристальної рентгенівської дифрактометрії встановлено наявність розворотів пакетів шарів росту до 3 arcsec для секторів {100} та {101}. Товщина пакетів шарів росту, що спостерігається, складає величину 20-30 мкм. Виявлено відносну зміну (у 6 разів) параметрів кристалічної решітки Δd/d у легованому кристалі щодо чистого кристала, яка обумовлене входженням наночастинок анатазу у межі пошарового росту з утворенням напівкогерентного зв'язку з кристалом. Показано, що у кристалічній матриці KDP спостерігається ефект гігантського нелінійно-оптичного відгуку наночастинок ана тазу. Методом снижения температуры впервые выращены кристаллы KDP из водных растворов содержащих нанокристаллы TiO₂ (анатаз). Концентрация TiO₂ варьировалась в исходном растворе от 10⁻³ до 10⁻⁵ М/л. в кристаллах KDP:TiO₂ методом трехкристальной рентгеновской дифрактометрии установлено наличие разворотов пакетов слоев роста до 3 arcsec для секторов {100} и {101}. Наблюдаемые толщины пакетов слоев роста составляют величину порядка 20-30 мкм. Обнаружено относительное изменение в (6 раз) параметров кристаллической решётки Δd/d в легированном кристалле относительно чистого кристалла, которое обусловлено вхождением наночастиц анатаза в границы послойного роста с образованием полукогерентной связи с кристаллом. Показано, что в кристаллической матрице KDP наблюдается эффект гигантского нелинейно-оптического отклика наночастиц анатаза.